Food Consumption Pattern in Rural Areas of Bangladesh (Bangladesh Journal of Public Administration, 2022)
The study was conducted to assess the food habit and dietary patterns of rural people in the Bogura district. A total of 37 households were considered as respondents for the study. A specially designed questionnaire was used as a tool for collecting data. The study revealed the rural people's family background, occupation, consumption patterns and average food intake of carbohydrates, protein, oil, fruits and other food items, factors affecting their food selection, and their satisfaction level regarding food under the specific objectives. The interviewees' mean household size was 5.19, whereas most respondents belonged to agricultural households (35.14%). It was found that rice essentially dominated the average daily food intake per person at 422.60 grams making up 52.37% of total food consumption and also constituted the most share of carbohydrate consumption. The respondent also consumes vegetables (185.10g/capita/day) and leafy vegetables (56.67g/capita/day) in moderate amounts but a lesser amount of fruits(35.45g/capita/day). Nutrition and price were the first and second determinants of food choice (16 and 15 of 37 households), and 54.06% of respondents were satisfied with their present food intake. Most households took protein four days a week, with the highest fish consumption (42.05g/capita/day) as of first preference. By conducting more awareness programmes on the importance of balanced food consumption, nutrition, quality food, and homestead gardening by the governmental agencies and non-governmental organizations working in the study area, the present scenario of quality food consumption can be improved.